Exploring Students’ Engagement in Learning Comparison through AI-Assisted Canva Games - Damanik, Debora Julia Elisabet; Rozi, Fahrur (International Journal of Language Teaching and Education, 2026)
The integration of technology in education has expanded rapidly, including the use of digital learning media to create more interactive and enjoyable learning experiences. One of these media is Canva, which has become a popular educational design platform. The novelty of this study lies in the use of Canva AI features to develop interactive learning media and create simple educational games more efficiently. This study aimed to explore student engagement in learning comparison through the use of AI-Assisted Canva Games. The research was motivated by students’ low interest and participation in conventional classroom learning. A descriptive qualitative method was employed, with data collected through observations, interviews, and documentation. The participants were 13 fifth-grade students from an elementary school in Simalungun Regency, North Sumatra, who participated in English learning using AI-Assisted Canva Games. The participants were selected purposively because they were directly involved in the implementation of the learning media. The findings revealed that AI-Assisted Canva Games enhanced student engagement by increasing students’ interest, participation, and active involvement during learning activities. Students reported that the games helped them understand the learning material more easily while creating a more enjoyable classroom atmosphere. In addition, teachers found it easier to design engaging and effective learning activities using Canva AI features. Overall, the findings indicate that AI-Assisted Canva Games can promote more innovative, interactive, and student-centered English learning by improving students’ engagement and supporting teachers in developing effective digital learning media.